Analysing Style and Autobiographical Element in Alice Munro’s “Dear Life” - Moayad Ahmad Alshara; Abdul Hameed Panhwar; Marwa Adel Hasan (European Scientific Journal, ESJ, 2017)
The paper aims to stylistically analyze the autobiographical elements in Alice Munro’s Story “Dear Life.” It is discovered that from the starting to the end of the story, it is full of the events which are very closely linked to Munro’s own life. Although the events have close resemblance to Munro’s life, these are factiously and artistically depicted so that they serve the purpose of literature and the stylistic aspects of the story. The researchers in the paper analyze and discuss the stylistic characteristics of the author with the help of the textual evidence from the story and to further support these, they cite the literature on the similar aspects. Finally, it is found that Munro’s fantastic style and the blend of the autobiographical facts and fiction make her story ‘Dear Life’ very interesting and worth reading.